30 years of East-West migration in Germany: A synthesis of the literature and potential directions for future research: - Matthias Rosenbaum-Feldbrügge; Nico Stawarz; Nikola Sander (Comparative Population Studies (CPoS), 2022)
The reunification of the socialist German Democratic Republic and the capitalist Federal Republic of Germany presents a unique setting for studying the impact of socio-economic and political change on migration. This paper provides a comprehensive review of the interdisciplinary literature on migration between East and West Germany since reunification, conducted in disciplines such as economics, demography, sociology, and human geography. We synthesise the literature with regard to data-related challenges as well as individual and contextual determinants of migration. We clarify some misinterpretations and discrepancies in previous studies, identify research gaps, and suggest directions for future research. Our review demonstrates that East-West migration mainly occurred in line with what could have been expected based on migration theory with regard to migrants' sex, age, education, labour market position, and social networks. West-East migration, in contrast, was strongly affected by return migrants who often stated non-occupational motives for moving. On the contextual level, differences in wages are better able to explain East-West migration over time than differences in unemployment rates. West-East migration, however, cannot be explained well with such macroeconomic models. This paper contributes a point of reference for future research on this topic, as well as on internal migration and socio-economic disparities in general.
urn:nbn:de:bib-cpos-2022-08en4
Keywords: 300; Internal migration; Return migration; Literature review; Economic disparities; Political transformation; German Democratic Republic; Macroeconomic factors; Individual-level determinants